Cognitive Symptom Management and Rehabilitation Therapy (CogSMART) for Traumatic Brain Injury. Treatment manual (ukrainian version). 1st part: sessions 1-4 - Twamley Елізабет; Noonan Сара; Savla Ґаурі; Schiehser Дон; Jak Емі; Assonov Дмитро; Ukrainska Яна; Komova Жанна; Osadchyi Артем; Chaban Олег; Khaustova Олена (Psychosomatic Medicine and General Practice, 2020)
CogSMART is a cognitive training program for people with traumatic brain injury (TBI). It aims to improve the skills of perspective memory, attention, executive functions (problem solving, planning, cognitive flexibility) in order to more successfully perform daily activities and achieve personal, work and study goals. CogSMART is based not on a large number of trainings and tasks, but on a compensatory cognitive training — improving cognitive skills by using certain adaptation strategies and removing obstacles. The use of CogSMART has already shown good results in the cognitive rehabilitation of people with traumatic brain injury in the United States. The translation of the manual was performed by specialists of the Kyiv City Clinical Hospital for War Veterans with further scientific editing of the text by professors of the Department of Medical Psychology, Psychosomatic Medicine and Psychotherapy at Bogomolets National Medical University. With the permission of Elizabeth Twamley, the author of the original program, the Ukrainian version of the manual is published in the journal and is available for Ukrainian-speaking audience. The program contains 12 sessions. This part of the Ukrainian version of the manual presents the first 4 sessions of CogSMART. Session 1 is introductory: participants learn about the structure of the program and its basic rules, talking about their traumatic brain injury experience and receive psychoeducation on the frequency, causes, mechanisms and symptoms of trauma, also get acquainted with the principles of cognitive training. Session 2 focuses on the skills of managing symptoms such as fatigue and sleep problems. Also it has psychoeducational components and relaxation strategies training. Session 3 covers issues such as headache, depression, anxiety, and post-traumatic stress disorder. In addition, the relaxation strategies training continues. Session 4 focuses on the problems of perspective memory. Participants who have problems with the ability to remember what needs to be done in the future will be able to learn how to solve them. This material can be useful for clinical psychologists, occupational therapists, psychotherapists and specialists in related fields who help people with traumatic brain injury.